Estudio del manejo agronómico de Pisum sativum L. en tres zonas agroecológicas de Santiago de Chuco, La Libertad - Castillo Villa, Blanca Fabiola (2019)
This research was conducted in three agroecological areas that include the hamlets of Huayatan, Cunguay and Julgas of the district and province of Santiago de Chuco, La Libertad between the months of April to July 2019, with the objective of describing the agronomic management of Pisum sativum L., for which 30 surveys were applied to farmers who plant peas, taking into consideration the size of the production units, quantity, quality and management of the seed, sowing time, sown varieties, land preparation modality, labor cultural, fertilization, irrigation, major pests, diseases and weeds, harvest time and production costs. This research was conducted in three agroecological areas that include the hamlets of Huayatan, Cunguay and Julgas of the district and province of Santiago de Chuco, La Libertad between the months of April to July 2019, with the objective of describing the agronomic management of Pisum sativum L., for which 30 surveys were applied to farmers who plant peas, taking into consideration the size of the production units, quantity, quality and management of the seed, sowing time, sown varieties, land preparation modality, labor cultural, fertilization, irrigation, major pests, diseases and weeds, harvest time and production costs. It is concluded that the farmers have 0.5 to 1 hectare dedicated to pea cultivation, use 6 cans per hectare (108 kg) and the seed comes from the previous harvest, the sowing season is in January and February, the most sown varieties are green, white, black eye, all respondents perform the same modality of land preparation such as fallow, cross, plow, champeo and planting, also executing weeding , incorporate 20 sacks of organic matter per hectare, sow the dry land and low irrigation; the pests and diseases that know and affect the crop are aphids, earthworms and root rot, weeds are the long sleeve, mustard, clover and Chilean, the harvested in green is done 3 months after sowing and dry grain 5 to 6 months and, no farmer records production costs.